Maritime Boundary Delimitation Settlement Strategy in East Segment II of the Singapore Strait Through the Three Stage Approach - Atika Thahira; Hendra Arjuna (SEAN Institute, 2025)
This research explores strategic legal pathways for addressing the unresolved maritime boundary delimitation in East Segment II of the Singapore Strait, a maritime area jointly bordered by Indonesia, Singapore, and Malaysia. The lack of formal delimitation in this segment has resulted in a jurisdictional vacuum, often referred to as a legal grey zone, which has significant implications for state sovereignty, international legal compliance, and regional maritime security. Through a qualitative legal analysis grounded in empirical research methods, this study investigates the intricate legal issues surrounding the Trijunction Point—a critical zone of overlapping claims. As a potential solution, the study supports the application of the Three-Stage Approach, comprising the construction of a provisional equidistance line, adjustment based on relevant geographic and legal considerations, and the application of a disproportionality test. Widely employed in international maritime adjudication, this method is recommended as a viable and equitable framework to facilitate legal certainty, foster regional cooperation, and uphold the rights and obligations of the littoral states involved.